Efficient adsorption of Cr (VI) from aqueous environments by phosphoric acid activated eucalyptus biochar. (1st March 2021) - Zeng, Huiting; Zeng, Honghu; Zhang, Hua; Shahab, Asfandyar; Zhang, Kang; Lu, Yanqin; Nabi, Iqra; Naseem, Faiza; Ullah, Habib
Abstract: Biochar, due to its ability to remediate heavy metals and organic contaminants from polluted water is considered as an economic adsorption material. This work involved pyrolysis driven eucalyptus carbon (EC) to produce eucalyptus activated carbon (AC) through a novel mechanism of using phosphoric acid (H3 PO4 ) and its subsequent testing for efficient adsorption of Cr (VI) from aqueous environments. Advanced characterization techniques like XRD, SEM, BET, FTIR, and XPS were employed to characterize the structure and composition of EC and AC. The AC could remove 99.76% of Cr(VI), which was higher than EC removal rate of 25.24%. The surface area of AC increased by almost 5 times 1265.56 m 2 /g compared to EC (253.25 m 2 /g). The removal rate of Cr(VI) was highly influenced by adsorption capacity, pH, adsorption time, temperature, kinetics, and isotherm. Reaction rate kinetics, isothermal, and thermodynamic analysis revealed that the adsorption curve of AC fits well with the quasi-second-order kinetic model. AC adsorption process was a spontaneous endothermic reaction limited by intraparticle diffusion and a combination of chemical and physical adsorption. Graphical abstract: Image 1 Highlights: Efficient removal of heavy metal Cr(VI) by phosphoric acid activated eucalyptus biochar. The removal mechanism of Cr(VI) was explored through FTIR and XPS. Activated biochar exhibited higher removal performance compared to pure biochar. A thermodynamic study showed that adsorption is a spontaneous endothermic process.